Contributions of lean production to the development of sustainable business practices in the food industry - Engström, Fredrik (2016)
Corporations in the food industry are under pressure from stakeholders to take responsibility for their social and environmental impact (Garnett, 2013). In the struggle, several initiatives have been implemented where the aim is to find a balance between financial, social as well as environmental aspects (Amani et al., 2015). Lean production is an initiative where the aim is to increase productivity and efficiency by the elimination of waste (Kovach & Cho, 2011). One of the cornerstones of lean production is to focus on a long term philosophy where value should be created for society as well as for the corporation (Liker, 2004). This means that if lean production is used as intended, it could lead to the creation of shared value. Shared value implicates that corporations take into account social, environmental and financial aspects when building strategies, and that focus should be on creating value in these three aspects (Porter & Kramer, 2011). Therefore, the aim in this study is to explain the role of lean production in developing sustainable business practices in the food industry.